Applications of measure of noncompactness for the solvability of an infinite system of second order differential equations in some integrated sequence spaces - Das,Rituparna (Universidad Católica del Norte, Departamento de Matemáticas, 2021)
Abstract The aim of this paper is to study the infinite system of second order differential equations along with the given boundary conditions for its solvability in some integrated sequence spaces. The result is achieved with the analytical tool namely the measure of noncompactness along with the idea of Meir-Keeler condensing operator and provides the realization of the sufficient conditions for the existence results in these Banach Sequence spaces. We also illustrate the results with examples.